Complexity Leadership: A study of Operationalizing Adaptive Leadership within the Resource Sector - Vyas, Alkesh Dahyalal (Curtin University, 2016)
The aim of this research was to gain a better understanding of the potential strategies for operationalizing Adaptive Leadership using Complexity Leadership Theory principles. Leading to a better understanding of the impact of such strategies on intellectual capital management and social capital of organisations within the natural resources sector in Western Australia. This research focused on the resources sector due to its significance to the Australian and in particular the Western Australian economy.